Predictors of Job Satisfaction Among County Jail Correctional Officers - Simmons, Richara (2017)
Job satisfaction among jail correctional officers is important because it ensures the continuity of officers who can promote and maintain a safe environment inside the jail for all staff and inmates. Most job satisfaction studies on correctional officers, however, are focused on prison officers and not county jail officers. The purpose of this correlational study was to test and extend Herzberg's Motivation-Hygiene theory by exploring job satisfaction and motivation among jail correctional officers in Miami-Dade Florida. Survey data were collected from 149 correctional officers using Specter's (1994) Job Satisfaction Survey. Data were analyzed through correlational and multiple regression analyses. Findings of the correlation results indicated positive relationships at the .05 level between the motivators and hygiene predictors with job satisfaction. Regression results indicated a statistically significant relationship between the motivators and hygiene predictors with job satisfaction (p = 0.00). The implications for social change include recommendations to jail administrators to provide channels through which their employees can inform them of prevalent issues to aid in increasing job satisfaction. Implementation of this recommendation may improve job satisfaction among jail correctional officers, thereby improving perceptions that the jail correctional officers are appreciated and trusted, increase their sense of self-sufficiency, improve morale problems, and help jail administrators invest in the well-being of current and future jail correctional officers that are needed to maintain the safety and security of correctional facilities